2018
DOI: 10.4081/vl.2018.7069
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic, quantitative comparison of lower extremity lymphedema versus normal control. Technical note with case reports

Abstract: Characterization of tissue by ultrasonography (CATUS) is a modern-day research endeavor intended to improve visual perception and image quantification. Visual perception increases with color. Quantification focuses on pixel echo brightnesses. A previously presented case report demonstrated reappearance of lymphatic channels a few days after manual drainage. Ultrasonographic images (US) of lymphatic leg and foot were quantitated and compared to a normal extremity based on proportions of pixels in specific brigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…These differences, also observed in this study, were observed in analyses conducted using CATUS to quantify echogenicity, which was lower in the lymphatic extremity, due to the presence of the lymphatic "lakes" and/or channels, which were hypoechogenic compared to the healthy limb. 11 Phan, Cherry, and Ryan 22 conducted a study with 12 patients with venous ulcers in the lower limbs, analyzing the dermis using mode B US. They found that dermal echogenicity was significantly reduced, indicating accentuated edema of the papillary dermis compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences, also observed in this study, were observed in analyses conducted using CATUS to quantify echogenicity, which was lower in the lymphatic extremity, due to the presence of the lymphatic "lakes" and/or channels, which were hypoechogenic compared to the healthy limb. 11 Phan, Cherry, and Ryan 22 conducted a study with 12 patients with venous ulcers in the lower limbs, analyzing the dermis using mode B US. They found that dermal echogenicity was significantly reduced, indicating accentuated edema of the papillary dermis compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…3 The CATUS software has been used to assess organs, such as the kidney before and after transplant, 2 and pathological changes, such as venous thrombosis, and can be used to classify aneurysms as acute or subacute, 8,9 to identify thrombus in the external carotid artery, 10 and to compare echogenic differences between limbs with lymphedema and healthy limbs. 11 The objective of the present article is to determine the ultrasonographic image analysis software parameters for differentiation of edema of venous origin from edema of lymphatic origin in lower limbs.…”
Section: Introductionmentioning
confidence: 99%